2013
DOI: 10.1002/oby.20047
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal salivary cortisol is associated with body mass index and waist circumference: The multiethnic study of atherosclerosis

Abstract: Objective: Neuroendocrine abnormalities, such as activation of the hypothalamic-pituitary-adrenal (HPA) axis, are associated with obesity; however, few large-scale population-based studies have examined HPA axis and markers of obesity. We examined the cross-sectional association of the cortisol awakening response (CAR) and diurnal salivary cortisol curve with obesity. Design and Methods: The Multiethnic Study of Atherosclerosis Stress Study includes 1,002 White, Hispanic, and Black men and women (mean age 65 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
143
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(159 citation statements)
references
References 41 publications
14
143
1
1
Order By: Relevance
“…As such, it is thus far unclear whether a consistent relationship exists between cortisol slope and either type of obesity. It does appear, however, that flatter, less sharply declining slopes are generally related to BMI and WHR, a finding supported by the strongest studies reviewed here (Champaneri et al, 2013;Steptoe et al, 2004). Both of these studies incorporate multiple sampling time points, which allows for a more precise slope measurement.…”
Section: Diurnal Cortisol Slopementioning
confidence: 51%
See 4 more Smart Citations
“…As such, it is thus far unclear whether a consistent relationship exists between cortisol slope and either type of obesity. It does appear, however, that flatter, less sharply declining slopes are generally related to BMI and WHR, a finding supported by the strongest studies reviewed here (Champaneri et al, 2013;Steptoe et al, 2004). Both of these studies incorporate multiple sampling time points, which allows for a more precise slope measurement.…”
Section: Diurnal Cortisol Slopementioning
confidence: 51%
“…Of note, this is the only study reviewed here that uses a longitudinal design which revealed that body size at baseline was positively associated with increases in cortisol concentrations seven years later without any increased BMI. Finally, one study found no relationship between BMI and total output, as measured by AUC (Champaneri et al, 2013).…”
Section: Total Daily Outputmentioning
confidence: 97%
See 3 more Smart Citations